If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c(5c + -6) = 0 Reorder the terms: 5c(-6 + 5c) = 0 (-6 * 5c + 5c * 5c) = 0 (-30c + 25c2) = 0 Solving -30c + 25c2 = 0 Solving for variable 'c'. Factor out the Greatest Common Factor (GCF), '5c'. 5c(-6 + 5c) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-6 + 5c)' equal to zero and attempt to solve: Simplifying -6 + 5c = 0 Solving -6 + 5c = 0 Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5c = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 5c = 0 + 6 5c = 0 + 6 Combine like terms: 0 + 6 = 6 5c = 6 Divide each side by '5'. c = 1.2 Simplifying c = 1.2Solution
c = {0, 1.2}
| (2x*2y)/2=48 | | -7m+9=29-m | | 600000=x-x/3 | | 98x-6x^2=0 | | 5.5/6=16.5/m | | 10+10d=9d | | -8a+2b=13 | | 39/4=r/12 | | (2x-5y)(3x+2y)= | | 8+3u=4u | | 8+3x=x+111+2x | | 1.3(6y-9)=2y+13 | | (f-7)(6f+7)=0 | | 6z=5z+9 | | 8x-11+2x=120 | | 4x-7=x+2x+3 | | 14x-(25x-18)=34x-(15-30)+18 | | 2y+17=5 | | 156=-16t^2+100t+20 | | 8b=9b-4 | | (h-3)(h-7)=0 | | -2(7-5k)-8k=-3k-4(k+8) | | 2.5=5(1-e^-((t-1)/10)) | | -3x+5y=#5 | | (-4x)2-34x+26=0 | | 2.5=5(1-e^-((t-1)/10) | | -8a+8-4a+3a+-7a= | | -2/15-1/4 | | =25i^2-20i+25 | | 15-9(9+10b)+(20b-4)=22 | | 8(1-4x)=-6(8+4x) | | w(w-5)=0 |